The Theoretical-Methodological Unit Of The Theater Of The Opressed Augusto Boal - Portes, Carolina Marcon (2023)
The purpose of this article was to analyze the method of the Theater of the Oppressed by Augusto Boal (1931-2009), trying to explain its theoretical-methodological unity from the perspective of human formation. We take as the main source of analysis, the book Games for Actors and Non-Actors (2008), where the theatrologist bases his method on examples of Forum Theater systematized, in the period of political exile lived in Europe, in the mid-1970s. We present Boal's interpretation of the categories "spectator" and "spect-actor" explaining who are the protagonists of the Theater of the Oppressed proposal. From the analysis of Boal's plays on the construction of atomic power plants, land reform and feminism, we highlight the pedagogical dimensions of his method in establishing relationships with classical approaches of the theater. We show that the content and methodology of the Theater of the Oppressed combine in the perspective of individual and social transformation of spectators into spect-actors. We conclude that about the pedagogical importance of theater in the formative process in that, by explaining situations of oppression among individuals, it promotes the development of human potentialities and consequently favors conditions of overcoming boundaries and conflicts.